Indian Women During the Japanese Occupation in Malaya, 1941-1945 - Nair, Syamala; Musa, Mahani (European Publisher, 2019)
Indians, regardless of class, endured hardship during the Japanese occupation, and the terrible encounter of Indians who lived in the estates were the most profound. Records of the Japanese occupation in Malaya and Singapore depicted women both as rivals of the Japanese and casualties of war. Studies on the Japanese treatment of Malayan women, particularly Indian women, however, have not merited much attention. This study examines how Indian women negotiated the Japanese occupation and their involvement in the Rani of Jhansi Regiment. The study utilises qualitative method using archival sources, newspapers, and recollections from witnesses and participants of the Indian nationalist movement. Documentary sources kept at the National Archives of Malaysia and Singapore, and the Singapore Oral History Centre provide glimpses of how Indian women managed wartime challenges, and how the Japanese attempted to mobilise them. While a few fought against the Japanese, others had benefitted from Japanese overtures when wartime experiences impacted their post-war careers. The predicament experienced during Japanese occupation and involvement in the nationalist movement had encouraged Indian women to participate in self-help organisations and political parties to enhance their lives in post-independence Malaya.